The distribution of green algae species from the Ulva genera (syn. Enteromorpha; Chlorophyta) in Polish inland waters - Messyasz, Beata; Rybak, Andrzej (University of Gdańsk, 2008)
Marine algae in inland waters in Poland have been rarely recorded. The distribution of 5 species and 1 subspecies of the Ulva genus (syn. Enteromorpha, Chlorophyta) observed in different inland aquatic ecosystems is reported. The algal distribution was established on the basis of the available literature, unpublished material, and oral reports. Information about the algal morphology and habitat conditions, from all of the 58 reported locations of ulvas in Poland, were assimilated and are presented here. The most widespread species of Ulva in inland waters in Poland was U. intestinalis (syn. Enteromorpha intestinalis) reported at 34 sites, while the rarest species was U. paradoxa (syn. Enteromorpha paradoxa), recorded at 2 sites. Species of Ulva have been reported at a range of inland aquatic ecosystems, but most commonly in lakes and small water-courses, such as ditches, channels and creeks. Most of the reported sites of penetration of Ulva (Enteromorpha) inland are concentrated in northwestern and central Poland.
Keywords: Enteromorpha; Ulva; Chlorophyta; Macroalgae; Distribution